Potensi Pohon Nipah dan Pemanfaatan terhadap Peningkatan Ekonomi Masyarakat Lokal - Hasaruddin Hasaruddin (Keizai, 2021)
Researchers conducted a study on Nipah Tree Potential and Utilization of Management to Improve the Economy of Local Communities. This study uses a qualitative approach, data analysis techniques that researchers use are in-depth interviews, observation, and documentation. The location of the research was carried out in the Tanjung Putri village community, South Arut sub-district, West Kotawaringin Regency. The research subjects were determined purposively, namely: (1) village heads and community groups who were business actors in the management of nipa palm trees; (2) community members. The following is a description of the research data, namely; Utilization that uses materials for building cottages for relaxing, as much as 58%. with direct sales, handicrafts in the form of baskets (Bakul), mats and hats as head protection, which utilizes Nipah shoots by 15%, then the community of stick broom craftsmen, which is as much as 35%. Meanwhile, for those who use as much as 40% of palm sugar, fruit that is made of fruit, and fro for additional iced cendol drinks, 45% of the Mayang Nipah portion is used as 5% consumption, development in terms of rejuvenation of nipa palm trees has not been maximized, also product development is very minimal due to lack of knowledge about the production of processed nipa palm fruit, this must then be a correction for policymakers to consider appropriate policy steps to improve economic conditions.